Penatalaksanaan Fisioterapi Pada Kasus Plantar Fasciitis: Efektivitas Kombinasi Tens, Ultrasound, Dan Terapi Latihan Di RS Kramat 128 - Zulfikar H. Wada; Caroline Xaveriana Dalla Soro; Ezra Bernadus Wijaya (JOURNAL SAINS STUDENT RESEARCH, 2026)
Plantar fasciitis is a musculoskeletal disorder characterized by heel pain and decreased foot function. This study aimed to evaluate the effectiveness of a multimodal physiotherapy approach combining Transcutaneous Electrical Nerve Stimulation (TENS), therapeutic ultrasound, and exercise therapy in patients with plantar fasciitis treated at the Physiotherapy Unit of RS Kramat 128. A descriptive case study design was employed involving three subjects who underwent eight treatment sessions over an eight-week period. Outcome measures included pain intensity assessed using the Visual Analogue Scale (VAS), ankle range of motion measured with a goniometer, muscle strength evaluated by Manual Muscle Testing (MMT), and functional ability assessed using the Foot and Ankle Ability Measure (FAAM). The results demonstrated clinical improvements in all subjects, including a mean pain reduction of 3, 6 points, increased ankle range of motion reaching normal reference values (20° dorsiflexion - 0° neutral, 35° plantarflexion), and improvements in muscle strength from grade 4 to grade 5. Variability in treatment response was influenced by adherence to home exercise programs, baseline physical condition, and lifestyle modifications. The findings suggest that a multimodal physiotherapy protocol combined with patient education and regular evaluation is effective in reducing symptoms and facilitating recovery in patients with plantar fasciitis.